2020
DOI: 10.24940/theijbm/2020/v8/i2/bm2002-057
|View full text |Cite
|
Sign up to set email alerts
|

Market Share as a Function of Board Diversity and Board Size of Selected Deposit Money Banks in Nigeria

Abstract: Market Share as a Function of Board Diversity and Board Size of Selected Deposit Money Banks in Nigeria 1. Introduction Banks Success has been the focus of academic and policy debate in developed and developing economies of the world. Deposit money banks around the world have been experiencing challenges over the years in the area of survival and market share. These challenges are attributable to weak or defective corporate governance mechanisms. The nature and mode of management and application of corporate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…This relationship is statistically significant meaning that Complementary alliances have a significant effect on the sustainability of MFIs in Cameroon thereby rejecting the main hypothesis which states that Complementary alliances do not significantly affect the sustainability of MFIs in Cameroon. This result is in consonance with the studies of Mwangi (2014), Almahdi (2019), Klus et al (2019), Maselo (2019), Wandia & Ismail (2019) Enyinnah et al (2020), Nshimiyiman (2021), who pinion that strategic alliance creation allow commercial banks, MFIs and other institutions to improve on their performance and long-term survival. These results in addition are common with the commercialisation relationship established by MFIs and other financial and non-financial institutions where the later enter into a partnership to provide sales services to the services of the former.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This relationship is statistically significant meaning that Complementary alliances have a significant effect on the sustainability of MFIs in Cameroon thereby rejecting the main hypothesis which states that Complementary alliances do not significantly affect the sustainability of MFIs in Cameroon. This result is in consonance with the studies of Mwangi (2014), Almahdi (2019), Klus et al (2019), Maselo (2019), Wandia & Ismail (2019) Enyinnah et al (2020), Nshimiyiman (2021), who pinion that strategic alliance creation allow commercial banks, MFIs and other institutions to improve on their performance and long-term survival. These results in addition are common with the commercialisation relationship established by MFIs and other financial and non-financial institutions where the later enter into a partnership to provide sales services to the services of the former.…”
Section: Discussionsupporting
confidence: 88%
“…Mersland and Urgeghe (2017) found that MFIs participating in alliances had higher financial performance and lower costs. In Lagos Nigeria, Enyinnah et al (2020) showed that strategic alliance dimensions have a significant and positive effect on market share. Klus et al (2019) established that in times of digitalization, firms increasingly need to form alliances due to the higher complexity and greater dynamics of the markets.…”
Section: Introductionmentioning
confidence: 99%